2015
DOI: 10.1128/jvi.00133-15
|View full text |Cite
|
Sign up to set email alerts
|

Nonglycosylated G-Protein Vaccine Protects against Homologous and Heterologous Respiratory Syncytial Virus (RSV) Challenge, while Glycosylated G Enhances RSV Lung Pathology and Cytokine Levels

Abstract: New efforts are under way to develop a vaccine against respiratory syncytial virus (RSV) that will provide protective immunity without the potential for vaccine-associated disease enhancement such as that observed in infants following vaccination with formalin-inactivated RSV vaccine. In addition to the F fusion protein, the G attachment surface protein is a target for neutralizing antibodies and thus represents an important vaccine candidate. However, glycosylated G protein expressed in mammalian cells has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 64 publications
8
44
1
Order By: Relevance
“…Therefore, it is unlikely that RSV G assumes distinct conformations without additional external stabilizing interactions. One form of stabilization may come from the oligomerization state of RSV G. It was previously suggested that RSV G exists as a trimer or tetramer (57,58). The extensive glycosylation of RSV G in the mucin-like regions flanking the CCD may also restrict RSV G flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is unlikely that RSV G assumes distinct conformations without additional external stabilizing interactions. One form of stabilization may come from the oligomerization state of RSV G. It was previously suggested that RSV G exists as a trimer or tetramer (57,58). The extensive glycosylation of RSV G in the mucin-like regions flanking the CCD may also restrict RSV G flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…Lung tissues were evaluated for perivascular eosinophil infiltration. Briefly, vessels with cellular infiltration (n ϭ 20/lung) were randomly selected by a masked pathologist, and the number of eosinophils was enumerated and averaged for a final score for each lung (52).…”
Section: Methodsmentioning
confidence: 99%
“…As a comparator, we used a G-ectodomain protein (residues 67–298) of RSV-A2 containing the CCD motif produced using E . coli (REG 67–298), which was previously found to generate protective immunity in mice and cotton rats [ 16 , 17 ]. We evaluated the immunogenicity of a CCD-deleted G-ectodomain [REG ΔCCD; with residues 172–186 replaced by a (Gly 4 Ser) 2 linker], and two large G subdomains covering the N-terminus (REG 67–163) and C-terminus (REG 187–298) upstream and downstream of the CCD, respectively, that were identified as immunodominant in the epitope profiling of post-RSV primary infection human sera ( Fig 1 panels A-B).…”
Section: Resultsmentioning
confidence: 99%
“…Neutralizing antibody titers represent 50% plaque inhibition. (F) SPR analysis of post-third vaccination serum antibodies (diluted 10-fold) binding to fully glycosylated G ectodomain RMG from RSV-A2 [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation